Utilização de amido de mandioca como espessante em bebida de soja - Drunkler, Northon Lee (2011)
The soy-based beverages have been presented as healthy alternative foods, with a growing market in Brazil. The cassava starch (Manihot esculenta, Crantz) is a low cost and highly available raw material in the Brazilian market and is widely used in food industry due to its functional properties resulting from the gelatinization process. In this work, commercial samples of soybean beverages produced with soybean extract were evaluated in relation to physicochemical and rheological properties and, the results were similar to those reported in the literature. The samples were evaluated considering their pH, total and soluble solids, lipids, protein, ash, and carbohydrates. For analyzing the rheological behavior, of both the commercial samples and the developed formulations, a Brookfield viscometer, model LDVII + PRO (673.7 dyne-cm maximum torque) was used. The average viscosity was determined at 8 ºC in speed ramps ranging from 50 to 200 rpm and 30 seconds of analysis at each speed; the values of consistency index and flow index were processed by the software Wingather® through the use of the power law model. The viscosimeter was equipped with the 18 spindle, small sample adaptor (15 mL volume) using an attached thermostated water bath. The highest values for viscosity, higher consistency index and lower fluidity index, were also found in the samples with the highest amount of total and soluble solids. New formulations were also developed with the aim of evaluating the effects of cassava starch and soybean extract concentrations on the apparent viscosity and sensory overall acceptance, using a 22 factorial design with three repetitions at the central point. Regarding the sensory analysis, the variables (cassava starch and soybean extract concentrations) had no significant effect at 5 % of probability. The treatment 1, which had a lower amount of both cassava starch and soybean extract showed the lowest score in relation to other treatments. Regarding apparent viscosity, however, these variables presented significant effect, where increasing soymilk and starch concentrations in the formulation resulted in an increased apparent viscosity of the final product. The physicochemical analysis carried out in the formulations included pH, total and soluble solids, lipids, protein, ash, and carbohydrates. Comparing the results of the developed formulations with those of the commercial products, it was possible to conclude that the physicochemical characteristics showed similar values, as well as the rheological behavior, and the beverages behaved as non-Newtonian slightly pseudoplastic fluids, in the same manner as already reported in other studies. The developed formulations were evaluated for the profile and amount of isoflavones, and the results were similar to those of other published studies, with predominance of conjugated glycosides over to the aglycone forms, and the total isoflavone contents ranged from 126.82 to 265.34 mg L-1 of freeze-dried extract . The cassava starch was added in relatively low amounts to the developed beverages (0.2 to 0.6%), but was enough to cause positive changes increasing the apparent viscosity and the sensory acceptance.